Finite element analysis(FEA) of fatigue case studies - Azrullah Aminullah (Nanyang Technological University, 2024)
To understand the importance and effectiveness of XFEM in crack studies through analysing simulation results from different Case studies. XFEM is studied to highlight the arsenal it has to overcome the gaps of FEM in crack simulation studies. This project aims to prove the effectiveness of XFEM in crack propagation studies by implementing its use in various case studies and analysing the outcomes. A total of five Case studies is done, with each of the Case studies experimenting with different aspects of XFEM. All of the Case studies were done using Finite Element Analysis software, ABAQUS. The different aspects of Case studies that is being experimented with XFEM in ABAQUS includes meshing element convergence, effects of Paris Law’s C and m constants, effects of different crack sizes. Finally, combining the findings and knowledge from all these Case studies into a final Case study of simulating an actual research study article done, comparing its simulation results and outcomes against the true experimental results from the research article to find out the capabilities of XFEM in simulating and predicting cracks through simulations. A conclusion was drawn from all the Case studies done in this project, that XFEM is proved to be a powerful tool for crack propagation analysis and studies.